2016
DOI: 10.1589/jpts.28.382
|View full text |Cite
|
Sign up to set email alerts
|

Medical complications experienced by first-time ischemic stroke patients during inpatient, tertiary level stroke rehabilitation

Abstract: [Purpose] The aim of this study was to assess the medical complications in first-time ischemic stroke patients, to identify the factors related to occurrence of complications. [Subjects and Methods] First-time ischemic stroke patients (n=81) admitted to a tertiary level inpatient rehabilitation center during a 5 year period were included in the study. The attending physiatrist noted the presence of specific medical complications and complications that required transfer to the acute care facility from patient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 60 publications
(82 reference statements)
3
35
1
3
Order By: Relevance
“…This subtype was also associated with better functionality and QoL. Indeed, post-discharge complications were more frequent in patients with TACS in previous studies 3. Arm and hand function in patients with TACS was significantly more compromised than that in patients with LACS and patients with PACS 32.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This subtype was also associated with better functionality and QoL. Indeed, post-discharge complications were more frequent in patients with TACS in previous studies 3. Arm and hand function in patients with TACS was significantly more compromised than that in patients with LACS and patients with PACS 32.…”
Section: Discussionmentioning
confidence: 66%
“…Stroke is the third most common cause of death in developed countries and the main cause of death in Latin America. Brazil stands out as having the highest rate of mortality from stroke in the Americas 3,4. In a recent study, the overall survival rate was 47% 5.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to focus on comorbidity and intercurrent diseases during geriatric stroke rehabilitation. The study cohort was characterised by a large drop in functional status after acute stroke, often with multiple comorbidities and a higher age compared to the majority of studies on stroke patients [ 5 10 , 12 – 14 , 26 ]. Although this subgroup had been triaged for inpatient geriatric rehabilitation, and selected as a vulnerable subgroup of patients on the base of medical complexity and functional dependency, discriminant factors were still present.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating complications during inpatient stroke rehabilitation found that 30–96% of the patients developed complications; this wide range could be due to different definitions of a complication and the methods of measurement [ 5 12 ]. The present study investigates intercurrent diseases, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation